Memory and Popular Graphics in the Public Space: A Chromatic Approach From Semiotics: un acercamiento cromático desde la semiótica - Yalán Dongo, Eduardo Enrique (2023)
This article analyzes the role of cultural memory through the chromatic plastic signs of the Peruvian popular graphic advertisement. The corpus considers the graphic-advertising production that circulates in the public space in downtown Lima, Peru. The qualitative reconstruction of the relationships between memory, space and chromatic plasticity is carried out through the semiotic gaze of a tensive approach, which allows us to appreciate the role of intensity in popular visual production. The reflection concludes in the contrast of the memory of retention of playful colors of the ghost sign versus a memory of functional color ostension of the urban popular graphics. This difference makes it possible to identify economic isotopies that promote the erosion of spatial and political rootedness with respect to the public.